The Effectiveness Of Use Of Rewards And Punishments In The Stad Cooperative Learning Method To Increase Motivation And Science Learning Outcomes Of Class 4 Students Of Kolursari II SDN Bangil - Dewi Nurjannah; Devita Sulistiana; Dian Puspita Anggraini (Universitas Islam Balitar, 2025)
The importance of using Reward and Punishment as a stimulus to improve learning outcomes and student motivation. This research aims to determine the effect of using Rewards and Punishments on motivation and learning outcomes. This type of quasi-experimental research design is